Signal processing first. - MacClellan, James H., ....-; Schafer, Ronald W., 1938-; Yoder, Mark A., ....- (Upper Saddle River : Pearson, 2003)
1. Introduction. 2. Sinusoids. 3. Spectrum Representation. 4. Sampling and Aliasing. 5. FIR Filters. 6. Frequency Response of FIR Filters. 7. z-Transforms. 8. IIR Filters. 9. Spectrum Analysis.